Accumulation of MxB/Mx2-resistant HIV-1 Capsid Variants During Expansion of the HIV-1 Epidemic in Human Populations - Wei Wei (EBioMedicine, 2016)
Recent studies have identified human myxovirus resistance protein 2 (MxB or Mx2) as an interferon induced inhibitor of HIV-1 replication. However, whether HIV-1 can overcome MxB restriction without compromise of viral fitness has been undefined. Here, we have discovered that naturally occurring capsid (CA) variants can render HIV-1 resistant to the activity of MxB without losing viral infectivity or the ability to escape from interferon induction. Moreover, these MxB resistant HIV-1 variants do not lose MxB recognition. Surprisingly, MxB resistant CA variants are most commonly found in the Clade C HIV-1 that is the most rapidly expanding Clade throughout the world. Accumulation of MxB resistant mutations is also observed during HIV-1 spreading in human populations. These findings support a potential role for MxB as a selective force during HIV-1 transmission and evolution.